2015
DOI: 10.1101/gad.256115.114
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles for the splicing regulator nSR100/SRRM4 during nervous system development

Abstract: Alternative splicing (AS) generates vast transcriptomic complexity in the vertebrate nervous system. However, the extent to which trans-acting splicing regulators and their target AS regulatory networks contribute to nervous system development is not well understood. To address these questions, we generated mice lacking the vertebrateand neural-specific Ser/Arg repeat-related protein of 100 kDa (nSR100/SRRM4). Loss of nSR100 impairs development of the central and peripheral nervous systems in part by disruptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
154
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(171 citation statements)
references
References 55 publications
13
154
0
Order By: Relevance
“…Importantly, all of these results were validated in knockout mice or by using in vivo knockdown strategies (Kusek et al 2012;Licatalosi et al 2012;Shibasaki et al 2013;Quesnel-Vallieres et al 2015;Vuong et al 2016). However, mice that are null for a given RNABP often exhibit pleiotropic phenotypes, which can make it difficult to explain a specific biological role through a single target RNA processing event.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, all of these results were validated in knockout mice or by using in vivo knockdown strategies (Kusek et al 2012;Licatalosi et al 2012;Shibasaki et al 2013;Quesnel-Vallieres et al 2015;Vuong et al 2016). However, mice that are null for a given RNABP often exhibit pleiotropic phenotypes, which can make it difficult to explain a specific biological role through a single target RNA processing event.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of nSR100 impairs neurite outgrowth and leads to neurodevelopmental defects in zebrafish and mice, consistent with nSR100's neuronal expression profile and its modulation of neural gene activities (Calarco et al, 2009;Quesnel-Valliè res et al, 2015;Raj et al, 2011). Widespread loss of nSR100 in a conditional nSR100/Srrm4 knockout mouse results in extensive (>85%) neonatal death, in part due to a respiratory defect (Quesnel-Valliè res et al, 2015).…”
Section: Nsr100/srrm4mentioning
confidence: 91%
“…The neural-specific SR-related protein of 100 kDa (nSR100/ Srrm4) is expressed specifically in neurons of multiple brain subregions and sensory organs (Calarco et al, 2009;Irimia et al, 2014;Nakano et al, 2012;Quesnel-Valliè res et al, 2015). nSR100 is highly conserved across vertebrates but is not found in invertebrates, suggesting that its emergence was associated with the increased regulatory and functional complexity of the vertebrate nervous system (Calarco et al, 2009).…”
Section: Nsr100/srrm4mentioning
confidence: 98%
See 1 more Smart Citation
“…Alternative mRNA isoforms may differ in open reading frames, thus impacting the function of the encoded protein, or may alter the presence of regulatory sequences in untranslated regions (UTRs) thereby influencing RNA stability, transport, or translational control (Nilsen and Graveley 2010). Importantly, tissue-specific differences in alternative splicing (AS) have been suggested to shape cell-fate decisions (Gehman et al 2012;Licatalosi et al 2012;Xue et al 2013;Raj et al 2014;Quesnel-Vallieres et al 2015), while signal-induced changes in AS have been observed in response to metabolic, neuronal, or immune cues (Patel et al 2001;Xie and Black 2001;Shin and Manley 2004;An and Grabowski 2007;Lynch 2007;Heyd and Lynch 2011;Martinez et al 2012;Fu and Ares 2014). Moreover, mutations that alter splicing have been causally linked to cancer, neurodegenerative diseases, and autoimmune disorders, among others (Jacobsen et al 2000;Cartegni and Krainer 2002;Cooper et al 2009;David and Manley 2010;Xiong et al 2014).…”
Section: Introductionmentioning
confidence: 99%